Runaway resorption of microcracks contributes to age-related hip-fracture patients - Marena Gray; Oliver Boughton; Crispin Wiles; Christina Reinhard; Nghia T. Vo; Robert Atwood; Richard Stavri; Justin P. Cobb; Ulrich Hansen; Richard L. Abel (Scientific Reports)
Abstract Microdefects, including microcracks and resorption trenches, may be important contributors to bone fragility. 3D microdefect morphology was imaged using synchrotron micro-CT to develop a classification system for investigating the relationship with bone mechanics and hip-fractures. Femoral heads from ageing hip-fracture patients (n = 5, 74–82 years) were compared to ageing non-fracture controls (n = 5, 72–84 years). Two trabecular cores were prepared from the chiasma; one was imaged using synchrotron micro-CT to measure microdefects and one was mechanically tested to measure tensile strength. Morphological and mechanical data were compared and correlated using Mann Whitney U test and Pearson’s rank correlation. All the procedures performed were in accordance with the ethical standards of the Imperial College Tissue Bank (R13004) and the 1984 Declaration of Helsinki. Microdefects varied and were classified into four categories based on shape and measurable parameters. Hip-fracture donors exhibited significantly higher density of all microdefects (p < 0.05). Microdefect volume was strongly negatively correlated with ultimate tensile strength (p < 0.05) and stiffness (p < 0.05). Microdefects might contribute to loss of bone strength and fragility fracture via runaway resorption. Microcracks could promote focussed osteoclastic resorption and the formation of resorption pits which create stress risers leading to the re-formation of microcracks under continued load. CT-based classification methods should be used to explore the complex interaction between microdefects, metabolism, and bone fracture mechanics.